2017
DOI: 10.1089/jmf.2016.0087
|View full text |Cite
|
Sign up to set email alerts
|

Blue Maize Extract Improves Blood Pressure, Lipid Profiles, and Adipose Tissue in High-Sucrose Diet-Induced Metabolic Syndrome in Rats

Abstract: The effect of blue maize extract in factors related to metabolic syndrome (MS) in Wistar rats was investigated. Total polyphenols, monomeric anthocyanins, and antioxidant activity were analyzed in blue maize. MS was induced in Wistar rats fed with high-sucrose (HS) diet for 12 weeks. During a period of 4 weeks, blue maize extract was administrated to HS groups fed with high-sucrose and high-cholesterol-high-sucrose (HS+C) diets. In the blue maize extract administered by orogastric cannulation, the levels of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 28 publications
2
15
0
2
Order By: Relevance
“…Our findings, thus, proved that fructose administration at this concentration and period produces an experimental model similar to MetS. This was in accordance with Johnson et al [35] ; Aydin et al [15] ; Mamikutty et al [50] ; Guzmán-Gerónimo et al [30] who demonstrated a relation between high fructose intake and MetS both in human and animal studies. Aydin et al [15] ; Mamikutty et al [50] confirmed that rats fed with a HFrD (10%-60%) can be used as an adequate animal model for human MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings, thus, proved that fructose administration at this concentration and period produces an experimental model similar to MetS. This was in accordance with Johnson et al [35] ; Aydin et al [15] ; Mamikutty et al [50] ; Guzmán-Gerónimo et al [30] who demonstrated a relation between high fructose intake and MetS both in human and animal studies. Aydin et al [15] ; Mamikutty et al [50] confirmed that rats fed with a HFrD (10%-60%) can be used as an adequate animal model for human MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Anthocyanin rich foods clearly illustrate the potential health benefits they contain through their impact in obesity and insulin‐resistance diseases. Recent studies have shown that a blue maize extract improved blood pressure, lipid profiles and adipose tissue in high‐sucrose diet‐induced metabolic syndrome in rats . Furthermore, different anthocyanin extracts from different dietary sources such as red orange, cherry juice, strawberry, black currant have been used in clinical trials with diabetic or overweight patients and a reduction in plasma LDL‐cholesterol, triglycerides, and body weight have been observed …”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their high polyphenol content, purple corn byproducts have been associated with several health properties such as antioxidant, anti-inflammatory, and antiglycative activity [2,10,[20][21][22][23]. Moreover, in vitro and in vivo studies demonstrate their capacity in the prevention of cardiovascular and type 2 diabetes risk factors by exerting a strong anti-hypertensive effect, lowering cholesterol level, ameliorating insulin resistance, and improving lipid profile in high-fat diet treated rats [24][25][26][27][28].However, it is well known that all these health benefits can occur only if the putatively active compounds are bioavailable. Bioavailability is markedly affected by bioaccessibility, i.e., the release of compounds after their intake with food, and by the chemical transformations occurring during gastrointestinal metabolism (digestibility factor) [29,30]; therefore, the evaluation of these two parameters is mandatory in order to adequately investigate the effectiveness of bioactive molecules in vitro [31,32].Recently, FlaNat Research Italia Srl (Rho, MI, Italy) developed a new Italian purple corn variety, named Moradyn, which is able to sprout and grow in northern Italy, maintaining a highly pigmented cob.…”
mentioning
confidence: 99%
“…Thanks to their high polyphenol content, purple corn byproducts have been associated with several health properties such as antioxidant, anti-inflammatory, and antiglycative activity [2,10,[20][21][22][23]. Moreover, in vitro and in vivo studies demonstrate their capacity in the prevention of cardiovascular and type 2 diabetes risk factors by exerting a strong anti-hypertensive effect, lowering cholesterol level, ameliorating insulin resistance, and improving lipid profile in high-fat diet treated rats [24][25][26][27][28].…”
mentioning
confidence: 99%